EFFECT OF SELECTIVE SEOTONIN REUTAKE INHIBITOR AND COGNITIVE BEHAVIOUR THERAPY COMBINED WITH SELECTIVE SEOTONIN REUTAKE INHIBITOR IN IMPROVING THE EMOTIONAL MATURITY OF CONVERSION DISORDER PATIENTS - iJain, Shubhangni; Jahan, Nudrat; Kataria , Dinesh (International Journal of Psychosocial Rehabilitation, 2020)
The aim of this research was to study comparative effectiveness of Selective Serotonin Reuptake Inhibitor (SSRI) alone and Cognitive Behaviour Therapy (CBT) combined with Selective Serotonin Reuptake Inhibitor (SSRI) in improving the emotional maturity of conversion disorder patients. Quasi- experimental research design was is followed for the research. A sample of 30 female patients with conversion disorder was selected. Tool used for this study is Emotional Maturity Scale (EMS) by R.R.Tripathi (1982) was administered on patients suffering from conversion disorder to see the pre-post intervention effect of SSRI alone and CBT+SSRI on emotional maturity. Study revealed that after the 12 weeks of interventions the outcome revealed that the effect of CBT+SSRI intervention was found more successful in improving the emotional maturity of conversion disorder patients.